In-hospital outcome and its predictors among patients with acute cardiogenic pulmonary oedema at a tertiary hospital in Harar, Eastern Ethiopia: a retrospective cohort study - Natanim Degefu; Abera Jambo; Lemma Demissie Regassa; Melaku Getachew (Taylor & Francis Group, 2024)
ABSTRACTBackground: Acute cardiogenic pulmonary oedema is highly associated with poor in-hospital outcomes. This study aimed to determine the in-hospital outcome and its predictors among patients with acute cardiogenic pulmonary oedema at a tertiary hospital in Harar, Eastern Ethiopia, from May 1 to 20, 2023.Methods: A retrospective cohort study was employed among 204 patients with acute cardiogenic pulmonary oedema who were admitted between 1st May 2018 and 30th April 2023. The collected data were entered into Excel, and analysed using theSTATA software version 17. The hazard ratio with its 95% confidence interval was used and a P-value < 0.05 was considered a statistically significant association.Results: The overall mortality rate was 17.60 (95% CI: 11.59-26.72) per 1000 person-day observation with mean (±SD) time to death was 2.88 (±2.06) days. Age (AHR: 1.35; 95% CI: 1.04-1.74 for every 10 years), being smoker (AHR: 3.26; 95% CI: 1.05-10.10), having respiratory rate of ≥40 breaths per minute (AHR: 5.46; 95% CI: 1.71-17.45), and having anaemia (AHR: 4.35; 95% CI: 1.23-15.33) were significant predictors of in-hospital mortality.Conclusion: More than one in ten patients in this study died in the hospital. Therefore, special attention needs to be considered for patients with those predictors of in-hospital mortality.